Buffeting performance of long-span suspension bridge based on measured wind data in a mountainous region - Yang, Yang; Gang, Yao; Wei, Fujia; Qin, Weihe (Journal of Vibroengineering, 2018)
Long-span suspension bridge increases rapidly in size as a result of bridge construction in a mountainous region, in addition, more and more long-span suspension bridges are in process of preparation. The bridge stiffness decreases with the increase of bridge span length, and hence the buffeting performance of bridge is sensitive to external factors. In this paper, the Cuntan Yangze Bridge located in a mountainous region is taken as the background to study the effect of different power spectrums on the buffeting performance. A three-dimensional finite element model is set up on the ANSYS platform. The fitted power spectrum of extreme strong wind is recorded and taken as the sample to analyze the buffeting performance. The results are compared with the specified power spectrum in the time and frequency domains. Different from existing studies, buffeting performances with the fitted power spectrum are larger than those with the specified power spectrum on the whole. Two kinds of power spectrum are coincidental in the overall tendency in the frequency domain and are distinct in the low frequency region. Structure performance of long-span suspension bridge in the mountainous region should be the subject of specially paid attention.